2008
DOI: 10.1007/s00428-008-0597-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic silencing of the FHIT gene in penile squamous cell carcinomas

Abstract: Methylation of normally unmethylated CpG-rich islands in or near the promoter region has been associated with transcriptional inactivation of tumor-suppressor and tumor-related genes in human cancers. However, so far, only a few studies have searched for DNA methylation in penile carcinoma (PC). On the other hand, human papillomavirus (HPV) has been reported to be associated with the pathogenesis of PC. To elucidate the methylation status of PC and HPV infection, the methylation status of eight genes (DAPK, FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…Previous studies have identified differentially methylated genes in penile cancer (14,15). These have been targeted studies in which candidate epigenetic-regulated genes have been identified, including RAS and THBS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified differentially methylated genes in penile cancer (14,15). These have been targeted studies in which candidate epigenetic-regulated genes have been identified, including RAS and THBS1.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the molecular genetics or epigenetics driving the development and progression of penile cancer. Aberrant methylation of a handful of candidate genes has previously been identified, including CDKN2A and RASSF1A (13)(14)(15)(16). Recently, epigenetic changes in both host and virus epigenomes have been reported in other HPV-induced cancers (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Publications containing less than five cases were also excluded from the analysis. A final total of 31 articles were included in this review12 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 45 (see table 1). …”
Section: Methodsmentioning
confidence: 99%
“…The FHIT gene, which spans the FRA3B fragile site at chromosome 3p14.2 [2] , has been found as an early and frequent event in a variety of malignant tumors [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%